Digital language learning with Duolingo: assessing its impact on listening, speaking, reading, and writing skills - Kazu, Ibrahim Yasar; Kuvvetli, Murat (Springer Heidelberg, 2026)
Language learning challenges highlight the need for innovative digital tools like Duolingo to improve proficiency and engagement. Therefore, this study addressed the critical demand for effective language learning tools among 10th grade (14-15 years old) high school students, focusing on the Duolingo website and its impact on four essential language skills. A mixed methods approach was employed, integrating a quasi-experimental design to quantitatively assess Duolingo's impact and a phenomenological design to qualitatively explore metaphorical perceptions and interview results. Additionally, a Repeated Measures ANOVA was used because it allows for comparing the means of the same participants across multiple tests. From a sample of 60 students, 32 were assigned to the experimental group, dedicating at least 1 h per week to learning English on Duolingo over 12 weeks, while the remaining 28 students formed the control group. Pre-tests, post-tests, and delayed tests based on Cambridge's language skills were given over three months, with the experimental group using Duolingo and the control group using traditional methods. Positive student feedback highlighted Duolingo's engaging, adaptive approach, leading to improvements in listening, speaking, reading, and writing skills in the experimental group. The findings affirmed the effectiveness of digital language learning tools like Duolingo and their potential to complement didactic language learning. Future studies could examine the long-term retention of language skills, compare Duolingo's effectiveness across age groups and proficiency levels, and explore its integration with traditional classroom instruction.
Keywords: Assessment; High school; Learning systems; Mixed-methods; Mobile learning